LOCAL FLAP TECHNIQUES OUTCOME FOR SACRAL PRESSURE ULCERS CLOSURES: A SYSTEMATIC REVIEW - Pratama, Yanuar Ari; Lakshya Nehal Samineni (Jurnal Rekonstruksi dan Estetik, 2025)
Highlights: Local flap reconstruction for sacral defects due to chronic pressure ulcers faces major challenges, including a high risk of infection, recurrence, and the complex sacral anatomy. Effective local flap techniques tailored to patient needs such as, the Clover Style, Modified Parasacral Bilobed, and Bilobed Flaps have been shown to improve both functional and aesthetic outcomes. Abstract: Introduction: Sacral pressure ulcers (PUs) pose a major challenge, especially in bedridden and elderly patients, due to risks like infection and delayed healing. Surgical reconstruction using local flaps offers effective defect closure with low donor-site complications. This systematic review analyzes local flap techniques for sacral PU reconstruction based on studies published from 2019 to 2024. Method: A comprehensive literature search was conducted in PubMed, selecting empirical studies that met predefined inclusion criteria. A total of seven studies were reviewed, comprising five case series and two case reports. Result: The findings highlight multiple local flap techniques, including the Clover-Style Fasciocutaneous Perforator Flap, Modified Parasacral Perforator-Based Bilobed Flap, and Bilobed Flap, each demonstrating favorable outcomes with high flap survival rates and minimal complications. These techniques offer advantages such as tension-free closure, enhanced vascularity, and reduced recurrence risk, making them viable alternatives for sacral PU management. Conclusion: Local flap reconstruction is a reliable and effective method for managing sacral pressure ulcers, with high success rates and good healing outcomes. Flap selection depends on defect size, patient condition, and surgeon expertise. A multidisciplinary approach involving preoperative imaging, wound care specialists, and physiotherapists can enhance surgical success. Further research, particularly randomized controlled trials, is needed to strengthen evidence-based flap selection criteria. Overall, local flaps remain the mainstay in sacral pressure ulcer reconstruction, contributing to improved patient quality of life.